A Structured, Debate-Style Cardiothoracic Surgery Journal Club for Trainee Acquisition and Application of Seminal Literature - Mara B. Antonoff; Tom C. Nguyen; Jessica G. Y. Luc; Clara S. Fowler; April Aultman Becker; Steven B. Eisenberg; Randall K. Wolf; Anthony L. Estrera; Ara A. Vaporciyan (Association of American Medical Colleges, 2016)
Abstract Introduction The acquisition of specialty-specific seminal literature and its application to daily, clinical patient-care decisions are critical components of clinical training. This structured, debate-style cardiothoracic surgery journal club module engages trainees in discussion of realistic patient scenarios, incorporating an extensive body of literature identified as the best evidence for the practice of cardiothoracic surgery. Methods We designed the structured, debate-style cardiothoracic surgery journal club and delivered it to University of Texas MD Anderson Cancer Center cardiothoracic surgery trainees. Overall assessment of knowledge acquisition consisted of both direct judging of debates by faculty facilitators and a year-end written test of trainee knowledge. Associated materials include guidelines and resources for faculty facilitators and trainees to prepare them for the journal club debate. Also included are cardiothoracic surgery patient cases, PowerPoint presentation slides, a debate score sheet, and multiple-choice knowledge tests with answer keys. Results Our structured, debate-style cardiothoracic surgery journal club is an effective educational intervention for cardiothoracic surgical trainees to gain practice in applying specialty-specific, literature-based evidence to particular patient problems. Discussion This resource may be used by course directors for surgery, for independent study by individuals planning to matriculate into surgical residencies, or as a review for those already in surgical training. Moreover, this curriculum can be delivered at other clinical training programs.